1998
DOI: 10.1097/00007435-199802000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Screening Women for Chlamydia trachomatis in Family Planning Clinics

Abstract: Compared with EIA screening, the strategy with the lowest program costs, a screening strategy that combines use of DNA amplification on cervical specimens in women receiving pelvic examinations, and DNA amplification of urine in women with no medical indications necessitating a pelvic examination, prevents the most cases of PID and provides the highest cost savings. With enhanced sensitivity over the other diagnostic assays and with the use of noninvasive specimen collection, DNA amplification assays should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
0
10

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(96 citation statements)
references
References 38 publications
2
84
0
10
Order By: Relevance
“…This rate is comparable to rates of asymptomatic infection among previously examined sexually active populations. [8][9][10][11][12][13][14][15] Urine-based screening was easy to integrate into emergency department service delivery and was well accepted by the emergency department client population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rate is comparable to rates of asymptomatic infection among previously examined sexually active populations. [8][9][10][11][12][13][14][15] Urine-based screening was easy to integrate into emergency department service delivery and was well accepted by the emergency department client population.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Previous screening studies have demonstrated high prevalence rates of asymptomatic chlamydial infection in family planning centers, adolescent health facilities, detention centers, school-and community-based clinics, and military settings. [8][9][10][11][12][13][14][15] The emergency department represents another health care access site for identifying persons with asymptomatic STIs. Many persons at risk for STIs use emergency departments as a primary source of health care.…”
mentioning
confidence: 99%
“…18,19 It is also supported by the high rate of chlamydia infections which are not associated with symptoms; up to 85% of uncomplicated chlamydia infections in women and up to 40% in men are asymptomatic, and as many as 60% of cases of chlamydial PID are without symptoms. 10,16 We suspect that many physicians do not have an appropriately high index of suspicion for testing for chlamydia.…”
Section: Discussionmentioning
confidence: 99%
“…9 In fact, as many as 30% of untreated or uncured Ct infections progress to PID, and each case of PID averages over $4,000 in future medical costs. 10 Rapid testing holds some promise in addressing this problem by reducing the number of lost-to-follow-up and thus untreated persons with Ct. 6 …”
Section: Introductionmentioning
confidence: 99%
“…De fato, estudos de custo-efetividade de exames para infecção por clamídia têm demonstrado que para cada dólar desembolsado em um exame existe uma economia de 12 dólares que seriam despendidos no tratamento das conseqüên-cias de uma infecção a longo prazo 5,6 . No Brasil, por outro lado, a detecção das DSTs não é um procedimento de rotina, sendo efetuada apenas quando as mulheres apresentam sintomas, e se há recursos disponíveis para o processamento dos espécimes.…”
Section: Introductionunclassified